A METHOD FOR MODELING A NEW EXPERIMENTAL MODEL OF PANCREATIC NECROSIS COMPLICATED BY SEPSIS - Abdurakhmanov, F.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
In our time, finding a more complex inflammatory disease of the abdominal organs in its pathogenesis is more difficult than acute pancreatitis. Over the past 50 years, acute pancreatitis ranks third among acute surgical diseases of the abdominal cavity and accounts for about 12.5% of all urgent pathology. At the same time, diagnostics and surgical tactics for pancreatic necrosis remain one of the far-fetched problems in urgent abdominal surgery. There is no doubt that this problem is related to the difficulties of prognosis and early diagnosis of destructive forms of acute pancreatitis. In the modern view of the mechanism of development of any variant of sepsis, the process associated with the development of the syndrome of systemic inflammatory reaction is put in the first place. At the same time, the presence of a purulent focus in the body, and even more so in the presence of organ dysfunction of at least one vital organ, corresponds to the full presentation of the verdict of surgical sepsis. It is based on these considerations that the main objectives of this article, reflecting the results of our study, were to develop an experimental model of pancreatic necrosis complicated by sepsis, in which the trigger will be the general reaction of the body that takes place in clinical practice.